Hegel entre liberais e conservadores:: o estudo histórico-filosófico de Domenico Losurdo - Machado, Alex (Temporalidades, 2021)
Often seen as a Liberal or Conservative, Georg W. F. Hegel is usually interpreted by two conceptual keys of the 20th century. From a historical-philosophical study, Domenico Losurdo aims to show how such a way of studying Hegel can be considered an error, thus proposing a new look at the german philosopher and his varied ideas and method of study and work.